Village du Kinh-Luoc - Pagode des Roses - Auteur inconnu (Wikimedia Commons, 1945)
Notice image issue de Wikimedia Commons. Titre: Village du Kinh-Luoc - Pagode des Roses. A postcard depicting the tomb of the Nguyn Dynasty Mandarin (and the Viceroy of Tonkin) Hoàng Cao Khi in the city of Hanoi, in the French protectorate of Tonkin.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale